High Performance and Stackable Trampoline Like‐Triboelectric Vibration Energy Harvester for In‐Situ Powering Sensor Node with Data Wirelessly Transmitted Over 1000‐m - Yu, Hongyong; Xi, Ziyue; Du, Hengxu; Yang, Hengyi; Qian, Zian; Guo, Xinyang; Guo, Yuanye; Huang, Yue; Du, Taili; Xu, Minyi (Advanced energy materials, 2024)
Addressing the power supply challenges of wireless sensor nodes is pivotal for advancing the development of the Internet of Things (IoT). This work proposes a high performance and stackable trampoline like‐triboelectric vibration energy harvester (T‐TVEH) that can efficiently harvest ultra‐wideband vibrational energy for in‐situ powering of sensor nodes. The unique structural design and material selection enables T‐TVEH to represent a breakthrough in terms of both working bandwidth and power density compared to recent research efforts of vibration energy harvesting. Specifically, the working bandwidth and the peak power density of T‐TVEH is 192 Hz and 5.9 W m−2, which are higher than previous related studies by 156% and 59.2%, respectively. Based on the excellent performance of the T‐TVEH, a wireless sensor node for monitoring machinery condition is constructed. Temperature, humidity, and frequency information are successfully acquired and transmitted to 1000‐m through the wireless sensor node, which is nine times improved compared to related studies. Meanwhile, it achieves fully self‐powered wireless operation monitoring and abnormal alarm on a real ship's marine diesel engine. Overall, this study proposed an innovative solution for in‐situ power supply of wireless sensor nodes, which has broad application prospects in the field of the IOT. This work proposes a high performance and stackable trampoline like‐triboelectric vibration energy harvester (T‐TVEH) that can efficiently harvest ultra‐wideband vibrational energy for in‐situ powering of sensor nodes. The T‐TVEH represents a breakthrough in terms of both working bandwidth and power density compared to recent research efforts in the field of vibration energy harvesting.